Isolating membrane and preparation method thereof, secondary battery and electric device
Patent Information
- Application Number
- CN202380045982.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-03-14
AI Technical Summary
The reliability and cycle performance of secondary batteries are insufficient in terms of high temperature and physical puncture, which causes the isolation film to easily delaminate and be punctured during use, affecting the stability and safety of the battery.
Design an isolation membrane, including a porous coating between a first porous base membrane and a second porous base membrane. The coating is composed of a binder and filling particles. The embedding depth of the filling particles is greater than or equal to 1 μm, which improves the performance of the membrane. The bonding force and heat resistance are improved, and an isolation film is formed under hot pressing conditions through a lamination process. The embedding depth of the filling particles in the porous base film with a high melting point is greater than that of the porous base film with a low melting point, optimizing the porosity and melting point. distributed.
It significantly improves the heat resistance and nail penetration performance of the isolation film, enhances the reliability and cycle performance of the secondary battery, reduces the risk of the isolation film being punctured, and improves the stability and safety of the battery.
Smart Images

Figure CN119631234A_ABST
Abstract
Description
Separator and preparation method thereof, secondary battery and electric device Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an isolation membrane and a preparation method thereof, a secondary battery, and an electrical device. Background Art
[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features of light weight, no pollution and no memory effect.
[0003] With the continuous development of the new energy industry, users have put forward higher requirements for the use of secondary batteries. The problem of improving the reliability of secondary batteries and power-consuming devices is currently in urgent need of solution.
[0004] Summary of the Invention
[0005] In view of the technical problems existing in the background technology, the present application provides an isolation membrane and a preparation method thereof, a secondary battery and an electrical device, aiming to improve the reliability performance of the secondary battery and the electrical device.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present application provides an isolation membrane, which includes a first porous base membrane; a second porous base membrane; and a porous coating layer, wherein the porous coating layer is arranged between the first porous base membrane and the second porous base membrane, wherein the porous coating layer includes a binder and filling particles, and the embedding depth of at least a portion of the filling particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filling particles in the second porous base membrane is greater than or equal to 1 μm.
[0007] Compared with the prior art, the present application includes at least the following beneficial effects: when the porous coating is located between the first porous base membrane and the second porous base membrane, the binder can not only play the role of bonding the first porous base membrane and the second porous base membrane, but also, at least a portion of the filling particles are embedded in the first porous base membrane and / or the second porous base membrane to a depth greater than or equal to 1 μm, thereby increasing the bonding force between the porous coating and the first porous base membrane and / or the second porous base membrane, effectively improving the heat resistance and nail penetration performance of the isolation membrane, thereby improving the reliability of the battery.
[0008] In any embodiment of the present application, the melting point of the first porous base membrane is higher than that of the second porous base membrane, and the embedding depth of the filler particles in the first porous base membrane is greater than the embedding depth of the filler particles in the second porous base membrane. When the separator meets this design, the battery can further achieve both good reliability and cycle performance.
[0009] In any embodiment of the present application, the embedding depth of the filling particles in the porous base membrane with a high melting point is recorded as D1, and the embedding depth of the filling particles in the porous base membrane with a low melting point is recorded as D2. The isolation membrane satisfies: 1.01≤D1 / D2≤3; optionally, 1.05≤D1 / D2≤2.
[0010] In any embodiment of the present application, the embedding depth of the filling particles in the first porous base membrane is greater than or equal to 1.5 μm, and can be optionally 2.0 μm-4.5 μm; and / or, the embedding depth of the filling particles in the second porous base membrane is greater than or equal to 1.1 μm, and can be optionally 1.1 μm-3.5 μm.
[0011] In any embodiment of the present application, the average pore size of the first porous base membrane is 0.1 μm-2 μm, optionally 0.1 μm-0.5 μm; and / or the average pore size of the second porous base membrane is 0.1 μm-2 μm, optionally 0.1 μm-0.35 μm.
[0012] In any embodiment of the present application, the volume average particle size Dv50 of the filling particles is 0.2 μm-1.2 μm, and can be optionally 0.3 μm-0.8 μm.
[0013] In any embodiment of the present application, the ratio of the porosity of the first porous base membrane to the porosity of the second porous base membrane is 1.01-3.5, and can be optionally 1.1-2.0.
[0014] In any embodiment of the present application, the porosity of the first porous base membrane is 40%-80%, optionally 40%-70%; and / or the porosity of the second porous base membrane is 20%-50%, optionally 25%-35%.
[0015] In any embodiment of the present application, the melting point of the first porous base membrane is 165°C-380°C, optionally 165°C-330°C; and / or the melting point of the second porous base membrane is 100°C-250°C, optionally 130°C-210°C.
[0016] In any embodiment of the present application, the binder includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.
[0017] In any embodiment of the present application, the filling particles include at least one of inorganic particles, organic particles, and organic-metal framework materials.
[0018] In any embodiment of the present application, the isolation film satisfies at least one of the following (1)-(3):
[0019] (1) The peel strength between the first porous base film and the porous coating layer is ≥5 N / m, and can be selected from 5.5 N / m to 10 N / m;
[0020] (2) The transverse heat shrinkage of the isolation film at 250°C for 1 hour is ≤1.5%, which can be optionally ≤1.0%;
[0021] (3) The longitudinal heat shrinkage rate of the isolation film at 250°C for 1 hour is ≤1.5%, and can be optionally ≤1.0%.
[0022] The second aspect of the present application provides a method for preparing an isolation membrane, comprising: providing a first porous base membrane and a second porous base membrane; preparing a porous coating slurry, the coating slurry comprising a binder and filling particles, and setting the porous coating slurry on the surface of the first porous base membrane and / or the second porous base membrane to form a porous coating; compounding the first porous base membrane and the second porous base membrane through a pressing process, so that the porous coating is set between the first porous base membrane and the second porous base membrane to obtain an isolation membrane, wherein the embedding depth of at least a portion of the filling particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filling particles in the second porous base membrane is greater than or equal to 1 μm.
[0023] In any embodiment of the present application, in the pressing process, the pressing temperature is 30°C-70°C, optionally 35°C-50°C; and / or the pressing pressure is 2N-30N, optionally 5N-20N.
[0024] A third aspect of the present application provides a secondary battery, which includes a separator prepared according to the method for preparing the separator of the first aspect or the second aspect of the present application.
[0025] In any embodiment of the present application, the secondary battery further includes a positive electrode sheet and a negative electrode sheet, and the separator is provided between the positive electrode sheet and the negative electrode sheet.
[0026] A fourth aspect of the present application provides an electrical device comprising the secondary battery according to the third aspect of the present application.
[0027] Since the device of the present application includes the secondary battery provided by the present application, it has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0029] FIG1 is a schematic structural diagram of an embodiment of an isolation membrane of the present application;
[0030] FIG2 is a schematic diagram of an embodiment of a secondary battery;
[0031] FIG3 is an exploded view of FIG2 ;
[0032] FIG4 is a schematic diagram of an embodiment of a battery module;
[0033] FIG5 is a schematic diagram of an embodiment of a battery pack;
[0034] FIG6 is an exploded view of FIG5;
[0035] FIG. 7 is a schematic diagram of an embodiment of a device using a secondary battery as a power source. DETAILED DESCRIPTION
[0036] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0037] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.
[0038] In the description herein, unless otherwise indicated, the term "or" is inclusive. That is, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0039] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” include the number itself, and “several” in “one or several” means two or more.
[0040] Unless otherwise specified, the terms used in this application have the commonly understood meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0041] secondary batteries
[0042] A secondary battery is a battery that can be recharged to activate the active materials after discharge and continue to be used.
[0043] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The separator is placed between the positive and negative electrodes to provide isolation. The electrolyte conducts ions between the positive and negative electrodes.
[0044] [Isolation film]
[0045] Referring to FIG1 , an embodiment of the present application provides a separator 10 comprising a first porous base membrane 11, a second porous base membrane 12, and a porous coating layer 13 disposed between the first and second porous base membranes 11, 12. The porous coating layer 13 comprises a binder 14 and filler particles 15, wherein at least a portion of the filler particles 15 is embedded in the first porous base membrane 11 to a depth greater than or equal to 1 μm and / or at least a portion of the filler particles 15 is embedded in the second porous base membrane 12 to a depth greater than or equal to 1 μm. Where a is the first embedding depth and b is the second embedding depth.
[0046] Without wishing to be limited to any theory, the isolation membrane of the specific structure of the present application can effectively improve the heat resistance, but there is a problem that the first porous base membrane and the second porous base membrane are easily delaminated during the use of the battery. After extensive research, the inventors found that when at least a portion of the filling particles 15 are embedded in the first porous base membrane 11 and / or the first porous base membrane 12 to a depth greater than or equal to 1 μm, the bonding force between the porous coating 13 and the first porous base membrane 11 and / or the second porous base membrane 12 is effectively increased, thereby improving the heat resistance of the battery; at the same time, the deeper interlocking structure can make the isolation membrane have a denser material layer, which increases the isolation membrane's ability to resist physical puncture, thereby further improving the reliability of the battery.
[0047] After further research, the inventors found that if the isolation membrane can optionally meet one or more of the following designs, the performance of the battery can be further improved.
[0048] In some embodiments, the melting point of the first porous base membrane 11 is higher than that of the second porous base membrane 12, and the embedding depth of the filler particles 15 in the first porous base membrane 11 is greater than the embedding depth of the filler particles 15 in the second porous base membrane 12. When this design is met, the separator can simultaneously achieve high tensile strength and local material density, effectively blocking lithium dendrites, thereby reducing the risk of separator puncture during battery cycling and further improving battery reliability.
[0049] In any embodiment of the present application, the embedding depth of the filling particles 15 in the porous base membrane with a high melting point is recorded as D1, and the embedding depth of the filling particles 15 in the porous base membrane with a low melting point is recorded as D2. The isolation membrane satisfies: 1.01≤D1 / D2≤3; optionally, 1.05≤D1 / D2≤2.
[0050] D1 / D2 may also be 1.01, 1.05, 1.3, 1.4, 1.45, 1.5, 1.83, 1.9, 2, 2.3, 2.4, 2.5, 2.53, 2.7, 2.84, 2.9, 3, etc., or a range consisting of any two of the above values, for example, 1.01-1.3, 1.05-1.5, 1.83-2, 2.3-2.53, 2.7-2.84, 2.9-3, etc. In some embodiments, D1 / D2 may also satisfy 1.05≤D1 / D2≤2.
[0051] In any embodiment of the present application, the embedding depth of the filling particles 15 in the first porous base membrane 11 is greater than or equal to 1.5 μm, and can be optionally 2.0 μm-4.5 μm; and / or, the embedding depth of the filling particles 15 in the second porous base membrane 12 is greater than or equal to 1.1 μm, and can be optionally 1.1 μm-3.5 μm.
[0052] The embedding depth of the filling particles 15 in the first porous base membrane 11 may be 1.5 μm, 1.6 μm, 1.65 μm, 2 μm, 2.2 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, etc., or a range consisting of any two of the above values, for example, 1.5 μm-1.65 μm, 2 μm-2.5 μm, 2 μm-3 μm, 2.5 μm-3.5 μm, 3.5 μm-4.5 μm, 2 μm-4.5 μm, etc. In some embodiments, the embedding depth of the filling particles 15 in the first porous base membrane 11 may be 2.0 μm-4.5 μm.
[0053] The embedding depth of the filling particles 15 in the first porous base membrane 12 may be 1.1 μm, 1.25 μm, 1.3 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, 2.3 μm, 2.6 μm, 2.95 μm, 3 μm, 3.2 μm, 3.3 μm, 3.5 μm, 4 μm, 5 μm, 6 μm, 7 μm, etc., or a range consisting of any two of the above values, for example, 1.1 μm-1.25 μm, 1.4 μm-2 μm, 1.8 μm-2.95 μm, 2 μm-3 μm, 1.1 μm-3.5 μm, etc. In some embodiments, the embedding depth of the filling particles 15 in the first porous base membrane 12 may be 1.1 μm-3.5 μm.
[0054] The embedding depth of the filling particles in the porous base film is a well-known meaning in the art and can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the isolation film is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and stuck on a sample table with conductive glue, and the sample slightly protrudes from the edge of the sample table. The sample stage is then placed in the sample holder and locked securely. The argon ion cross-section polisher (e.g., IB-19500CP) is powered on and vacuumed (e.g., 10 Pa to 4 Pa). The argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours) are set. The sample stage is then adjusted to rocking mode and polishing begins. After polishing, a scanning electron microscope (e.g., ZEISS Sigma300) is used to obtain an ion polished cross-sectional morphology (CP) image of the sample to be tested. The thickness of the base film and coating are measured separately. The EDS mapping mode is then selected to measure the distribution depth of the element (e.g., aluminum) contained in the filler particles in the base film as the embedment depth. For example, the coating thickness can be substituted using the midpoint of the curve distribution as the dividing line. The coating thickness values on both sides of the midline are removed, which is the initial value. The value is then extended to the point where the content of the element (e.g., aluminum) contained in the filler particles reaches zero. The value is then read, which is the embedment depth.
[0055] In any embodiment of the present application, the average pore size of the first porous base membrane is 0.1 μm-2 μm, optionally 0.1 μm-0.5 μm; and / or the average pore size of the second porous base membrane is 0.1 μm-2 μm, optionally 0.1 μm-0.35 μm.
[0056] The average pore size of the first porous base membrane 11 may be 0.1 μm-2 μm, for example, 0.1 μm, 0.12 μm, 0.2 μm, 0.4 μm, 0.5 μm, 0.65 μm, 0.85 μm, 1 μm, 1.2 μm, 1.35 μm, 1.5 μm, 1.75 μm, 1.85 μm, 2 μm, etc., or a range consisting of any two of the above values, for example, 0.1 μm-0.2 μm, 0.4 μm-0.85 μm, 1 μm-1.35 μm, 1.5 μm-1.75 μm, 1.85 μm-2 μm, etc. In some embodiments, the average pore size of the first porous base membrane 11 may be 0.1 μm-0.5 μm.
[0057] The average pore size of the second porous base membrane 12 may be 0.1 μm-2 μm, for example, 0.1 μm, 0.15 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.75 μm, 0.85 μm, 1 μm, 1.2 μm, 1.5 μm, 1.75 μm, 1.85 μm, 2 μm, etc., or a range consisting of any two of the above values, for example, 0.1 μm-0.2 μm, 0.1 μm-0.35 μm, 0.3 μm-0.75 μm, 0.85 μm-1.2 μm, 1.5 μm-1.75 μm, 1.85 μm-2 μm, etc. In some embodiments, the average pore size of the second porous base membrane 12 may be 0.1 μm-0.35 μm.
[0058] When the average pore size of the first porous base membrane and the average pore size of the second porous base membrane meet the above conditions, the isolation membrane can meet the embedding depth of the present application while also having good tensile strength.
[0059] In any embodiment of the present application, the average pore size of the porous base membrane is measured using a mercury porosimeter with reference to GB / T 21650.1-2008.
[0060] In any embodiment of the present application, the volume average particle size Dv50 of the filling particles 15 is 0.2 μm-1.2 μm, and can be optionally 0.3 μm-0.8 μm.
[0061] The volume average particle size Dv50 of the filler particles 15 may be 0.2 μm to 1.2 μm, for example, 0.2 μm, 0.35 μm, 0.4 μm, 0.5 μm, 0.65 μm, 0.75 μm, 0.85 μm, 0.9 μm, 1 μm, 1.2 μm, etc., or a range formed by any two of the foregoing values, for example, 0.2 μm to 0.35 μm, 0.4 μm to 0.65 μm, 0.3 μm to 0.8 μm, 0.5 μm to 0.85 μm, 0.75 μm to 1 μm, etc. In some embodiments, the volume average particle size Dv50 of the filler particles 15 may be 0.3 μm to 0.8 μm.
[0062] The volume average particle size Dv50 of the filler particles is well known in the art and represents the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%. It can be measured using methods known in the art. For example, it can be measured using a laser particle size analyzer (such as the Malvern Master Size 3000) in accordance with the standard GB / T 19077-2016.
[0063] In any embodiment of the present application, the ratio of the porosity of the first porous base membrane 11 to the porosity of the first porous base membrane 12 is 1.01-3.5, and can be optionally 1.1-2.0.
[0064] The ratio of the porosity of the first porous base membrane 11 to the porosity of the first porous base membrane 12 can be 1.01, 1.5, 1.8, 2, 2.15, 2.5, 2.87, 3, 3.01, 3,15, 3.2, 3.25, 3.4, 3.5, etc., or a range consisting of any two of the above values, for example, 1.01-1.8, 2-2.5, 2.87-3, 3.01-3.2, 3.25-3.5, etc.
[0065] When the ratio of the porosity of the first porous base membrane 11 to the porosity of the first porous base membrane 12 meets the above conditions, the separator can meet the embedding depth of the present application while having good tensile strength.
[0066] In any embodiment of the present application, the porosity of the first porous base membrane 11 is 40%-80%, optionally 40%-70%; and / or the porosity of the first porous base membrane 12 is 20%-50%, optionally 25%-35%.
[0067] The porosity of the first porous base membrane 11 may be 40%, 50%, 55%, 58%, 60%, 65%, 70%, 72%, 73.5%, 75%, 80%, etc., or a range consisting of any two of the above values, for example, 40%-50%, 55%-58%, 60%-70%, 72%-73.5%, 75%-80%, etc. In some embodiments, the porosity of the first porous base membrane 11 may be 40%-70%.
[0068] The porosity of the first porous base membrane 12 may be 20%, 25%, 28.5%, 30%, 32%, 40%, 45%, 48%, 50%, or a range consisting of any two of the above values, for example, 20%-25%, 25%-35%, 30%-40%, 45%-50%, etc. In some embodiments, the porosity of the first porous base membrane 12 may be 25%-35%.
[0069] The porosity of the base film is well known in the art and can be tested using equipment and methods known in the art. For example, the porosity of the base film can be tested using a mercury porosimeter in accordance with GB / T 21650.1-2008.
[0070] In any embodiment of the present application, the melting point of the first porous base membrane 11 is 165°C-380°C, optionally 165°C-330°C; and / or the melting point of the first porous base membrane 12 is 100°C-250°C, optionally 130°C-210°C.
[0071] The melting point of the first porous base membrane 11 may be 165° C., 169° C., 170° C., 176° C., 180° C., 212° C., 235° C., 256° C., 264° C., 280° C., 315° C., 330° C., 355° C., 360° C., 365° C., 380° C., or a range consisting of any two of the above values, for example, 165° C.-176° C., 180° C.-212° C., 235° C.-280° C., 315° C.-330° C., 355° C.-360° C., 365° C.-380° C., etc. In some embodiments, the melting point of the first porous base membrane 11 may be 165° C.-330° C.
[0072] The melting point of the first porous base membrane 12 is 100° C., 110° C., 125° C., 135° C., 141° C., 145° C., 150° C., 155° C., 160° C., 170° C., 185° C., 195° C., 200° C., 210° C., 220° C., 230° C., 240° C., 250° C., or a range consisting of any two of the above values, for example, 100° C.-125° C., 135° C.-141° C., 145° C.-155° C., 160° C.-185° C., 195° C.-210° C., 130° C.-210° C., 220° C.-250° C., etc. In some embodiments, the melting point of the first porous base membrane 12 may be 130° C.-210° C.
[0073] The melting points of the first and second porous base membranes can be tested using equipment and methods known in the art. For example, differential scanning calorimetry can be used for measurement. For details, reference can be made to standard GB / T 19466.3-2004. As an example, the measurement can be performed as follows: 4-6 mg of the sample to be tested is placed in the sample chamber of a differential scanning calorimeter. The temperature is raised from 25°C to 400°C at a rate of 10°C / min. The melting endothermic curve of the sample is obtained, and the temperature corresponding to the peak of the curve is the melting point of the sample.
[0074] In any embodiment of the present application, the binder 14 includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.
[0075] The first porous base film 11 and the second porous base film 12 can be directly laminated by hot pressing. During the hot pressing process, if the temperature is too high, the porosity will be small and the air permeability will be poor; if the temperature is too low, the first porous base film 11 and the second porous base film 12 will not be firmly bonded. Therefore, it is necessary to adjust the hot pressing temperature appropriately. Optionally, the hot pressing temperature is 20°C-50°C.
[0076] When the porous coating layer 13 is disposed between the first porous base film 11 and the second porous base film 12 , and the binder 14 in the porous coating layer 13 includes the above components, the stability of the secondary battery can be improved.
[0077] In any embodiment of the present application, the filling particles 15 include at least one of inorganic particles, organic particles, and organic-metal framework materials.
[0078] Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0079] Alternatively, the inorganic particles having a dielectric constant of 5 or more may include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3)O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling the adhesive layer to have a more stable and more uniform structure; in addition, by selecting a coupling agent, surfactant or polymer with a specific functional group to modify the inorganic particles, it is also helpful to improve the adhesive layer's wetting and retention properties for the electrolyte, and improve the adhesiveness of the adhesive layer to the first porous base membrane and the second porous base membrane.
[0080] Alternatively, the inorganic particles having ion conductivity but not storing ions may include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following: 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion conductivity of the isolation membrane.
[0081] Alternatively, the inorganic particles capable of undergoing electrochemical reaction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0082] Alternatively, the organic particles may include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, a cellulose modifier (e.g., carboxymethyl cellulose), a melamine resin, a phenolic resin, a polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), a silicone resin, a polyimide, a polyamideimide, a polyaromatic amide, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyaryletherketone, a copolymer of butyl acrylate and ethyl methacrylate (e.g., a cross-linked polymer of butyl acrylate and ethyl methacrylate).
[0083] Optionally, the organic-metal framework material may include one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.
[0084] In some embodiments, the content of the binder may be greater than or equal to 10%, optionally 10%-30%, based on the total weight of the adhesive layer.
[0085] In some embodiments, the content of the filler may be less than or equal to 90%, optionally 40%-90%, 60%-80%, based on the total weight of the adhesive layer.
[0086] In some embodiments, the coating may further include a dispersant, such as carboxymethyl cellulose, to adjust the viscosity of the coating slurry and improve the quality and uniformity of the coating.
[0087] In some embodiments, the content of the dispersant may be less than or equal to 25%, optionally less than or equal to 20%, based on the total weight of the adhesive layer.
[0088] When a porous coating layer 13 is provided between the first porous base membrane 11 and the second porous base membrane 12, and the filling particles 15 in the porous coating layer 13 include at least one of the above-mentioned inorganic particles, organic particles, and organic-metal framework materials, the filling particles 15 in the porous coating layer 13 can further improve the heat resistance and physical properties of the isolation membrane 10, thereby improving the stability of the secondary battery.
[0089] In any embodiment of the present application, the isolation film 10 satisfies at least one of the following (1)-(3):
[0090] (1) The peel strength between the first porous base film and the second porous base film is ≥5 N / m, which can be 5.5 N / m-10 N / m;
[0091] (2) The transverse heat shrinkage of the isolation film at 250°C for 1 hour is ≤1.5%, which can be optionally ≤1.0%;
[0092] (3) The longitudinal heat shrinkage rate of the isolation film at 250°C for 1 hour is ≤1.5%, and can be optionally ≤1.0%.
[0093] When at least one of the above (1) to (3) of the separator 10 satisfies the given range, the separator 10 has good heat resistance and physical properties, thereby improving the stability of the secondary battery.
[0094] The transverse and longitudinal thermal shrinkage rates of the separator 10 are both well-known in the art and can be measured using methods known in the art. For example, sample preparation involves punching the separator prepared above into samples with a width of 50 mm and a length of 100 mm. Five parallel samples are placed on A4 paper and secured. The A4 paper containing the samples is then placed on corrugated paper with a thickness of 1 mm to 5 mm.
[0095] Sample test: Place A4 paper on corrugated paper into a blast oven, set the oven temperature to 250°C, and start timing after the temperature reaches the set temperature and stabilizes for 30 minutes. After the set time (1 hour in this application) is reached, measure the length and width of the isolation film, and mark the values as a and b respectively.
[0096] Calculation of thermal shrinkage: Transverse direction (TD) thermal shrinkage = [(50-b) / 50] × 100%, longitudinal direction (TD) thermal shrinkage = [(50-a) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0097] In any embodiment of the present application, the preparation method of the isolation membrane includes: providing a first porous base membrane and a second porous base membrane; preparing a porous coating slurry, the coating slurry includes a binder and filling particles, setting the porous coating slurry on the surface of the first porous base membrane and / or the second porous base membrane to form a porous coating, and compounding the first porous base membrane and the second porous base membrane through a pressing process so that the porous coating is set between the first porous base membrane and the second porous base membrane to obtain an isolation membrane, wherein the embedding depth of at least a portion of the filling particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filling particles in the second porous base membrane is greater than or equal to 1 μm.
[0098] In any embodiment of the present application, in the pressing process, the pressing temperature is 30°C-70°C, optionally 35°C-50°C; and / or the pressing pressure is 2N-30N, optionally 5N-20N.
[0099] During the lamination process, the lamination temperature may be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, etc., or a range consisting of any two of the above values, for example, 30°C-40°C, 40°C-50°C, 35°C-50°C, 50°C-60°C, etc. In some embodiments, the lamination temperature is 35°C-50°C.
[0100] The pressing pressure may be 2N, 5N, 7N, 10N, 12N, 15N, 17N, 20N, 23N, 55N, 27N, 30N, etc., or a range consisting of any two of the above values, for example, 2N-10N, 5N-20N, 10N-25N, 15N-30N, etc. In some embodiments, the pressing pressure is 5N-20N.
[0101] By controlling the temperature and pressure in the pressing process within the above-mentioned range, the embedding depth of at least a portion of the filling particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filling particles in the second porous base membrane is greater than or equal to 1 μm, thereby effectively increasing the bonding force between the porous coating and the first and second porous base membranes, improving the heat resistance of the isolation membrane, and thereby improving the reliability of the secondary battery.
[0102] Unless otherwise specified, all raw materials used in the separator (eg, the first porous base membrane, the second porous base membrane, the binder, the filler, etc.) can be purchased commercially.
[0103] [Positive electrode]
[0104] In a secondary battery, a positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0105] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil.
[0106] There is no limitation on the specific type of the positive electrode active material. Active materials known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can select according to actual needs.
[0107] As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, olivine-structured lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.
[0108] The modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.
[0109] The positive electrode film layer usually optionally includes a binder, a conductive agent and other optional additives.
[0110] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive carbon black (Super P, SP), graphene, and carbon nanofibers.
[0111] As an example, the binder can be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0112] [Negative electrode]
[0113] In a secondary battery, a negative electrode plate generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0114] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0115] The specific type of negative electrode active material is not limited, and active materials that can be used for the negative electrode of a secondary battery known in the art can be used, and those skilled in the art can make a selection according to actual needs. As an example, the negative electrode active material may include, but is not limited to, one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. Silicon-based materials can be selected from one or more of elemental silicon, silicon oxides (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials can be selected from one or more of elemental tin, tin oxides, and tin alloys. These materials can all be obtained commercially.
[0116] In some embodiments, to further increase the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0117] The negative electrode film layer usually optionally includes a binder, a conductive agent and other optional auxiliary agents.
[0118] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0119] As an example, the binder may be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0120] As an example, other optional auxiliary agents may be thickening and dispersing agents (such as carboxymethylcellulose sodium, CMC-Na), and PTC thermistor materials.
[0121] [Electrolyte]
[0122] Secondary batteries may include an electrolyte that conducts ions between a positive electrode and a negative electrode. The electrolyte may include an electrolyte salt and a solvent.
[0123] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0124] As an example, the solvent may be selected from ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl darbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), n-propyl propionate (NP), propylene glycol (PEG), propylene glycol (PP), propylene glycol (C1), propylene glycol (C2), propylene glycol (C3), propylene glycol (C4), propylene glycol (C5), propylene glycol (C6), propylene glycol (C7), propylene glycol (C8), propylene glycol (C9), propylene glycol (D1), propylene glycol (D2), propylene glycol (D3), propylene glycol (D4), propylene glycol (D5), propylene glycol (D6), propylene glycol (D7), propylene glycol (D8), propylene glycol (D9), propylene glycol (D10), propylene glycol (D11), propylene glycol (D12), propylene glycol (D13), propylene glycol (D14), propylene glycol (D15), propylene glycol (D16), propylene glycol (D17), propylene glycol (D18), propylene glycol (D19), propylene glycol (D20), propylene glycol (D21), propylene glycol (D22), propylene glycol (D23), propylene glycol (D24), propylene glycol (D25), propylene glycol (D26), propylene glycol (D27), propylene glycol (D28), propylene glycol (D29), propylene glycol (D31), propylene glycol (D32), propylene glycol (D33), propylene glycol (D34), propylene glycol (D35), propylene glycol (D36), propylene glycol (D37), propylene glycol (D38), propylene glycol (D39), propylene One or more of the group consisting of propionate (PP), methyl butyrate (Methyl Butyrate MB), ethyl butyrate (Ethyl Butyrate, EB), 1,4-butyrolactone (1,4-Butyrolactone, GBL), tetramethylene sulfone (SF), dimethyl sulfone (Methyl Sulfone, MSM), methyl ethyl sulfone (Methyl Ethyl Sulfone, EMS) and diethyl sulfone (Diethyl Sulfone, ESE).
[0125] In some embodiments, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.
[0126] In some embodiments, the secondary battery may be a lithium-ion secondary battery. When the porous coating layer 13 is located between the first porous base membrane 11 and the second porous base membrane 12, the binder 14 not only serves to bond the first porous base membrane 11 and the second porous base membrane 12, but also, at least a portion of the filler particles 15 are embedded in the first porous base membrane 11 and / or the second porous base membrane 12 to a depth of greater than or equal to 1 μm, thereby increasing the bonding strength between the porous coating layer 13 and the first porous base membrane 11 and the second porous base membrane 12, thereby improving the reliability of the secondary battery.
[0127] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG2 shows a secondary battery 5 with a square structure as an example.
[0128] In some embodiments, the secondary battery may include an outer packaging for encapsulating the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0129] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0130] In some embodiments, referring to FIG3 , the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 51 may have an opening communicating with the receiving cavity, and the cover 53 may be positioned over the opening to seal the receiving cavity.
[0131] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator 10, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator 10, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, dried and injected with electrolyte, and then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell. Multiple battery cells can also be further connected in series, in parallel, or mixed to form a battery module. Multiple battery modules can also be connected in series, in parallel, or mixed to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.
[0132] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0133] The battery module 4 may further include a housing having a housing space, and the plurality of secondary batteries 5 may be housed in the housing space.
[0134] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0135] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0136] [Installation]
[0137] The present application also provides an electrical device, which includes the secondary battery of the present application. The battery cell, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck), an electric train, a ship and a satellite, and an energy storage system.
[0138] The device can select battery cells, battery modules or battery packs according to its usage requirements.
[0139] Figure 7 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0140] As another example, an electric device may be a mobile phone, a tablet computer, or a laptop computer. Such an electric device is generally required to be lightweight and thin, and may use a battery cell as a power source.
[0141] The beneficial effects of the present application are further illustrated below with reference to the examples.
[0142] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0143] 1. Preparation of isolation membrane
[0144] Isolation film 1:
[0145] (1) Providing a first porous base membrane and a second porous base membrane: the first porous base membrane is polypropylene (PP), and the second porous base membrane is polyethylene (PE); wherein the melting point of the first porous base membrane is 165°C, and the melting point of the second porous base membrane is 135°C; the porosity of the first porous base membrane is 55%, and the porosity of the second porous base membrane is 35%; the average pore size of the pore structure of the first porous base membrane is 0.15 μm, and the average pore size of the second porous base membrane is 0.12 μm.
[0146] (2) Preparation of coating slurry: The binder polyacrylate and the filler particles aluminum oxide and carboxymethyl cellulose were mixed uniformly in a suitable amount of deionized water as a solvent in a ratio of 1:4:1 to prepare a coating slurry. The volume average particle size Dv50 of the filler particles was 0.3 μm.
[0147] (3) The above coating slurry was applied to one surface of a PE base film to form a porous coating, and the coating was dried in an oven for 8 seconds. The PP and PE base films were then hot-pressed at a temperature of 45°C, a pressure of 10N, and a time of 5 seconds, so that the porous coating was formed between the PP base film and the PE base film to form a separator. The depth of the aluminum oxide particles embedded in the first porous base film PP was 1.2 μm, and the depth of the aluminum oxide particles embedded in the second porous base film PE was 1.1 μm.
[0148] The preparation methods of isolation membranes 2-12 are similar to those of isolation membrane 1, except that the average pore size of the base membrane or one or more of the hot pressing processes are adjusted, as detailed in Table 1. Other preparation methods are consistent with those of isolation membrane 1.
[0149] The isolation membrane 1 prepared by the above method was subjected to relevant performance tests, and the specific results are shown in Table 1.
[0150] 2. Preparation of batteries
[0151] Example 1
[0152] 1. Preparation of positive electrode sheet
[0153] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (SuperP), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and cutting processes.
[0154] 2. Preparation of negative electrode sheet
[0155] The negative electrode active material artificial graphite, conductive agent carbon black (SuperP), binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0156] 3. Isolation film
[0157] The isolation film used was the isolation film 1 prepared above.
[0158] 4. Preparation of electrolyte
[0159] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:70 to obtain an organic solvent. Fully dried electrolyte salt LiPF6 is dissolved in the above mixed solvent. The concentration of the electrolyte salt is 1.0 mol / L. After mixing evenly, an electrolyte solution is obtained.
[0160] 5. Preparation of secondary batteries
[0161] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0162] The preparation methods of the secondary batteries of Examples 2-10 and Comparative Examples 1-2 are similar to those of the secondary battery of Example 1, except that different isolation membranes are used (Example 1-10 uses isolation membrane 1-10, and Comparative Example 1-2 uses isolation membrane 11-12). See Table 1 for details.
[0163] 3. Battery performance test
[0164] 1. Transverse heat shrinkage test at 250℃:
[0165] Sample preparation: The prepared isolation film was punched into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on A4 paper and fixed. The A4 paper with the samples was then placed on corrugated paper with a thickness of 1 mm to 5 mm.
[0166] Sample test: Place A4 paper on top of corrugated paper into a blast oven. Set the oven temperature to 250°C. After the temperature reaches the set temperature and stabilizes for 30 minutes, start timing. After the set time (e.g., 1 hour), measure the width of the separator. The value is marked as b.
[0167] Transverse direction (TD) thermal shrinkage = [(50-b) / 50] x 100%, and the average value of 5 parallel samples is taken as the test result.
[0168] 2. Nail penetration test
[0169] Test at 25°C and 100% SOC. Place the battery in the order of thermal insulation pad / puncture cell / thermal pad / cell to be tested / thermal pad. Connect the high-temperature temperature-sensitive line and start the water circulation in advance. When the temperature of the large surface of the cell stabilizes at 25°C, continue to circulate for more than 10 minutes. Use a φ3mm high-temperature resistant steel needle, facing the center of the heat source, and puncture at a speed of 0.01mm / s until the cell to be tested fails (the instrument displays a voltage fluctuation or a sharp drop). Record the time. The puncture cell refers to a punctured cell used as a heat source.
[0170] As can be seen from Table 1, by analyzing Examples 1-10 and Comparative Examples 1-2, the depth of the filling particles embedded in the first porous base membrane and / or the second porous base membrane in Examples 1-10 is greater than or equal to 1 μm, which effectively improves the heat resistance of the isolation membrane and the nail penetration test performance of the battery, thereby effectively improving the reliability of the secondary battery.
[0171] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present application, and such modifications or substitutions should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.
Claims
1. A separation film, comprising: a first porous base membrane; a second porous base membrane; A porous coating layer, wherein the porous coating layer is arranged between the first porous base membrane and the second porous base membrane, wherein the porous coating layer includes a binder and filler particles, and the embedding depth of at least a portion of the filler particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filler particles in the second porous base membrane is greater than or equal to 1 μm.
2. The isolation film according to claim 1, characterized in that The melting point of the first porous base membrane is higher than that of the second porous base membrane, and the embedding depth of the filler particles in the first porous base membrane is greater than the embedding depth of the filler particles in the second porous base membrane.
3. The isolation film according to claim 1 or 2, characterized in that: The embedding depth of the filling particles in the first porous base membrane is recorded as D1, the embedding depth of the filling particles in the second porous base membrane is recorded as D2, and the isolation membrane satisfies: 1.01≤D1 / D2≤3; optionally, 1.05≤D1 / D2≤2.
4. The isolation film according to any one of claims 1 to 3, characterized in that: The embedding depth of the filling particles in the first porous base film is greater than or equal to 1.5 μm, and can be optionally 2.0 μm-4.5 μm; and / or, The embedding depth of the filling particles in the second porous base membrane is greater than or equal to 1.1 μm, and can be optionally 1.1 μm-3.5 μm.
5. The isolation film according to any one of claims 1 to 4, characterized in that: The average pore size of the first porous base membrane is 0.1 μm-2 μm, and can be 0.1 μm-0.5 μm; and / or the average pore size of the second porous base membrane is 0.1 μm-2 μm, and can be 0.1 μm-0.35 μm.
6. The isolation film according to any one of claims 1 to 5, characterized in that: The volume average particle size Dv50 of the filling particles is 0.2 μm-1.2 μm, and can be optionally 0.3 μm-0.8 μm.
7. The isolation film according to any one of claims 1 to 6, characterized in that: The ratio of the porosity of the first porous base membrane to the porosity of the second porous base membrane is 1.01-3.5, and can be optionally 1.1-2.
0.
8. The isolation film according to any one of claims 1 to 7, characterized in that: The porosity of the first porous base film is 40%-80%, and can be 40%-70%; and / or, The porosity of the second porous base membrane is 20%-50%, and can be optionally 25%-35%.
9. The isolation film according to any one of claims 1 to 8, characterized in that: The melting point of the first porous base membrane is 160°C-380°C, and can be 165°C-330°C; and / or the melting point of the second porous base membrane is 100°C-250°C, and can be 130°C-210°C.
10. The isolation film according to any one of claims 1 to 9, characterized in that: The binder includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.
11. The isolation film according to any one of claims 1 to 10, characterized in that: The filling particles include at least one of inorganic particles, organic particles, and organic-metal framework materials.
12. The isolation film according to any one of claims 1 to 11, characterized in that: The isolation film satisfies at least one of the following (1)-(3): (1) The peel strength between the first porous base film and the porous coating layer is ≥5 N / m, which can be 5.5 N / m-10 N / m; (2) The transverse heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.5%, and can be optionally ≤1.0%; (3) The longitudinal heat shrinkage rate of the isolation film at 250° C. for 1 hour is ≤1.5%, and can be optionally ≤1.0%.
13. A method for preparing an isolation film, comprising the following steps: providing a first porous base membrane and a second porous base membrane; Prepare a porous coating slurry, the coating slurry includes a binder and filler particles, and place the porous coating slurry on the surface of the first porous base film and / or the second porous base film to form a porous coating; The first porous base membrane and the second porous base membrane are compounded by a lamination process so that the porous coating layer is disposed between the first porous base membrane and the second porous base membrane to obtain the isolation membrane, wherein: The embedding depth of at least a portion of the filling particles in the first porous base membrane is greater than or equal to 1 μm and / or the embedding depth of at least a portion of the filling particles in the second porous base membrane is greater than or equal to 1 μm.
14. The preparation method according to claim 13, characterized in that: In the lamination process, the lamination temperature is 30°C-70°C, and can be 35°C-50°C; and / or, The pressing pressure is 2N-30N, and can be 5N-20N as an option. 15 . A secondary battery comprising the separator according to claim 1 or the separator prepared by the method for preparing the separator according to claim 13 or 14.
16. The secondary battery according to claim 15, characterized in that: It also includes a positive electrode sheet and a negative electrode sheet, and the isolation film is arranged between the positive electrode sheet and the negative electrode sheet.
17. An electrical device comprising the secondary battery according to claim 15 or 16.
Citation Information
Cited By
Lithium battery diaphragm with modified barium titanate composite coating and preparation method of lithium battery diaphragm
CN121566057A